Experimental investigation of electrochemical carbon dioxide reduction reaction for C1 products with diatomic copper manganese electrocatalyst - Hee, Zachary An (Nanyang Technological University, 2023)
Using copper as a homonuclear single-atom catalyst, or SAC, as a cathode in an electrochemical cell, increases the selectivity and faradaic efficiency. However, it does not produce enough CO2 reduction reaction activity, or CO2 RR. A higher activity of CO2RR means higher amount of CO2 gas used in the reaction to produce chemical products such as formic acid. Substituting a homonuclear SAC with a hetero-diatomic catalyst, it produces unique catalytic properties like higher faradaic efficiency and performance. Adding manganese with copper as a hetero-diatomic catalyst, manganese can suppress the water reduction reaction for more CO2 reduction activity to occur.